The utility of mean platelet volume as a predictor of postoperative atrial fibrillation following coronary artery bypass grafting - Çayır, Mustafa Çağdaş (Journal of Surgery and Medicine, 2020)
Aim: Atrial fibrillation is the most common arrhythmia following coronary artery bypass grafting (CABG). The predictors of postoperative atrial fibrillation (POAF) following CABG are controversial. The aim of this study was to evaluate the predictivity of mean platelet volume (MPV) in the development of atrial fibrillation following CABG and other risk factors affecting POAF. Methods: A total of 227 patients who underwent on-pump CABG in the cardiovascular surgery department of our hospital between May 2016 and January 2019 were included in this retrospective cohort study. Patients were divided into two groups as those who underwent POAF and those who did not (non-POAF group). Patients’ demographic data such as age, gender, height, weight and BMI, biochemical parameters, comorbidities, smoking status, ejection fraction, the number of bypassed vessels, the use of intra-aortic balloon pump and inotropic agents, total drainage, neurological and other complications, operation time, duration of admission in intensive care unit and in the ward, and mortality status were recorded and comparatively analyzed. Results: No statistically significant differences were found between the groups in terms of gender, body mass index, the incidences of diabetes mellitus, hypertension, chronic obstructive pulmonary disease, pulmonary arterial hypertension, renal failure, smoking status, the number of bypassed vessels, the use of intra-aortic balloon pump, inotropic agents, and biochemical parameters (P<0.05 for all) except red cell distribution width (RDW), urea and mean platelet volume (MPV). MPV, RDW and urea values were significantly higher in the POAF group (P=0.004, P=0.018 and P=0.006, respectively). Multivariate regression analysis revealed that age, MPV and the amount of total drainage were independent risk factors for developing POAF (OR=1.080, OR=1.371, OR=1.001; P=0.001, P<0.001, P=0.024, respectively). Conclusion: MPV can be used as a predictor for the development of POAF following on-pump CABG. MPV is a quite simple parameter, which can be readily obtained in routine complete blood count. However, our results should be supported by further prospective, multicenter and large-scale studies.